Stability analysis of a delay differential Kaldor's model with government policies - Caraballo, Tomás; Silva, Alex Pereira da (MATHEMATICA SCANDINAVICA, 2020)
This paper is devoted to analysis of the stability of the economy according to an extended version of Kaldor's economic growth model. We consider the role of the government and its simultaneous monetary and fiscal policies and we study whether or not a time delay between the recognition and the implementation of its fiscal policy can affect the economic stability. Numerical simulations provide further conclusions about the long-term behavior of the four variables modeled—namely, national income, capacity of production, bonds value and money supply.